1999
DOI: 10.1046/j.1365-2141.1999.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a continuous decline in haemopoietic cell function from birth: application to evaluating bone marrow failure in children

Abstract: There are considerable differences in haemopoietic activity between young children and adults on the one hand, and between adults and the elderly on the other. A fundamental unanswered question is whether these differences relate to discrete stages or are part of a continuous process. We have sought to define aspects of the haematological ageing process, and have found that results from children with bone marrow failure syndromes differ from age-matched reference values. Haemopoietic cells were obtained from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 23 publications
1
50
0
2
Order By: Relevance
“…Wilson et al [8] showed that dormant HSCs are not just resting but deeply inactive as they have reduced metabolism, ribosomal biogenesis, and DNA replication. There is further evidence for a continuous decline in stem cell function from birth [40]. The mechanism for this was recently described as the misorientation of centrosomes with age, leading to a reduction in the correct establishment of asymmetric stem cell division with respect to its niche [41].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al [8] showed that dormant HSCs are not just resting but deeply inactive as they have reduced metabolism, ribosomal biogenesis, and DNA replication. There is further evidence for a continuous decline in stem cell function from birth [40]. The mechanism for this was recently described as the misorientation of centrosomes with age, leading to a reduction in the correct establishment of asymmetric stem cell division with respect to its niche [41].…”
Section: Discussionmentioning
confidence: 99%
“…Progenitor cell pool which plays the role of a pluripotent precursor reserve decreases with age (Bagnara et al 2000). The ability of the progenitor pool to self-maintenance diminishes too (Marley et al 1999). Chronic radiation exposure as a stress factor can lead to different degrees of hematopoietic insufficiency manifested by elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in the HSC compartment can be induced-for example through diseases, chemotherapy, transplantation, cytokine treatment, and aging. 43,34,[44][45][46][47][48][49][50][51][52][53] After such events the HSC compartment can become pauciclonal.…”
Section: A Clonal Diversity Model Of the God Of Hscmentioning
confidence: 99%